What reforms for Europe without a reform for european representative democracy? - Arena, Antonio Ignazio (Diritto Pubblico Europeo - Rassegna online, 2023)
The essay is dedicated to the (almost complete) absence of a parliamentary initiative of legislative acts at European level. This absence reflects the origin of EU and the ‘hybrid nature’ of the European institutional system (neither federal State nor international organization). Nevertheless, in the paper, it is argued that the absence of a parliamentary initiative of legislative acts is not coherent with some fundamental principles of the EU Law. Without the legislative initiative (at least as a rule), the European Parliament is not autonomous and therefore the principle of separation of powers is not respected. Moreover, the individual members of the European Parliament or the parliamentary minorities are unable to take the initiative. In the conclusions, it is observed that the eventual further development of European integration should require the full realisation of the representative democracy in Europe